2000
DOI: 10.1155/2000/705436
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of Children′s and Parents′ Memory for a Novel Painful Experience

Abstract: BACKGROUND: Despite recent progress in understanding memory of pain in adults, the validity of the assumption that these findings extend to children has not been established. Because treatment often is evaluated on the basis of pain recall, it is crucial that the accuracy of pain memories in children be established.OBJECTIVES: To examine children's ability to recall pain intensity and contextual details associated with a novel painful experience. Furthermore, children's memories were compared with those of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 33 publications
2
18
0
Order By: Relevance
“…3,43,44,69 This research indicates that children can accurately recall previously experienced pain over a period of months or even years. For example, Badali et al 3 examined 5-to 12-year-old children's memory of reported pain intensity for pain from a cold pressor task, which requires children to immerse their hand in cold water for as long as they can.…”
Section: Situational and Methodologic Influencesmentioning
confidence: 80%
See 1 more Smart Citation
“…3,43,44,69 This research indicates that children can accurately recall previously experienced pain over a period of months or even years. For example, Badali et al 3 examined 5-to 12-year-old children's memory of reported pain intensity for pain from a cold pressor task, which requires children to immerse their hand in cold water for as long as they can.…”
Section: Situational and Methodologic Influencesmentioning
confidence: 80%
“…What is the consequence of recalling painful experiences on management of subsequent medical experiences in childhood and adulthood? With respect to children, much of what we know concerns recall of stressful experiences, rather than recall of the experience of pain itself (with a few exceptions 3,43,69 ). A body of evidence shows that stressful invasive procedures are recalled quite accurately over delays of between 6 weeks and many years.…”
Section: No Patternmentioning
confidence: 99%
“…Previous memory research has used time frames ranging from one week to one year [2; 9]. Parents and children completed the memory interviews out of earshot of each other so as to not bias their recall.…”
Section: Methodsmentioning
confidence: 99%
“…Parents and children completed the memory interviews out of earshot of each other so as to not bias their recall. The memory assessment followed a similar protocol to that used with children and adolescents examining children’s memory for venipuncture [25] and cold pressor pain [2; 22; 23]. Prior to answering the four memory questions, children and parents were asked to first recall when they/their child were at home in the first few weeks following surgery.…”
Section: Methodsmentioning
confidence: 99%
“…Some researchers have adapted various kinds of tanks (eg, insulated picnic chests, Figs 1 and 2) with 2 compartments separated by a plastic or metal filter. 3,9,16,25,33,34,42,47 In an apparatus of this type, one compartment holds ice and water, and the other, the immersion tank, holds water alone so that the child's hand never comes into direct contact with ice. A pump causes water to flow (continuously or as needed) between the 2 compartments, a process that helps to keep the water near the target temperature and prevents the development of a microenvironment of warm water around the child's hand.…”
Section: Equipmentmentioning
confidence: 99%